2021
DOI: 10.3390/ijerph18116067
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the COVID-19 Outbreak on Mental Health Outcomes among Youth: A Rapid Narrative Review

Abstract: The coronavirus disease (COVID-19) outbreak has affected not only physical health but also mental health and psychological wellbeing. This narrative review aimed to map the literature on the psychological impact on the young generation of the COVID-19 pandemic, social restrictions, and extraordinary measures to curb the spread of coronavirus. We performed a systematic search of MEDLINE through PubMed and Web of Science [Science Citation Index Expanded, SCI-EXPANDED), Social Sciences Citation Index (SSCI), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 42 publications
2
65
0
2
Order By: Relevance
“…Deng and colleagues [9] found that most COVID-19 patients experience depression, anxiety, and sleep disturbances. Cielo and colleagues [11] found a negative psychological impact on, and high vulnerability in, the young in the context of developing psychological distress. The adaptation of the C19PS [15] confirmed the original structure proposed by the authors (20 items distributed by four factors-psychological, psychosomatic, economic, and social factors), although item 20 ("I am unable to curb my anxiety of catching coronavirus from others"), in the original version, saturated in factor 4 (social factor), and in this study, it saturated in factor 1 (psychosomatic factor).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deng and colleagues [9] found that most COVID-19 patients experience depression, anxiety, and sleep disturbances. Cielo and colleagues [11] found a negative psychological impact on, and high vulnerability in, the young in the context of developing psychological distress. The adaptation of the C19PS [15] confirmed the original structure proposed by the authors (20 items distributed by four factors-psychological, psychosomatic, economic, and social factors), although item 20 ("I am unable to curb my anxiety of catching coronavirus from others"), in the original version, saturated in factor 4 (social factor), and in this study, it saturated in factor 1 (psychosomatic factor).…”
Section: Discussionmentioning
confidence: 99%
“…This unsettling scenario has several direct and indirect effects, including on physical and mental health [7][8][9]. The outbreak has a psychological impact on individuals and society [10], as has been reported in different studies, namely, regarding depression, anxiety, stress [7,11], risk-attitudes [12], fear [13], perceived risk [14] and coronophobia [15]. In fact, Deng and colleagues [9] found that 45% of COVID-19 patients experience depression, 47% anxiety and 34% sleep disturbances.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many analyses performed in different parts of the world have shown that the emotional distress experienced during the pandemic mainly influenced people from younger age groups. A meta-analysis of the research on emotional well-being of young people during the pandemic [36] showed that they are much more threatened with the risk of experiencing anxiety, stress, and depression than older people. In addition, young people experienced problems with sleeping [37], somatization disorders, and obsessive-compulsive disorders [38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one of the predictors of positive emotions was combining work with studies. On the one hand, the simultaneous fulfillment of two tasks is a great challenge, especially due to the risk of losing a job to which young people working in services are often exposed, and due to dynamic changes in the system of education (the necessity to deal with the requirements of online education) [36]. On the other hand, the necessity to fulfil tasks in two social contexts at the same time increases the probability of maintaining social relationships and weakens the sense of isolation, which is one of the sources of anxiety and other disorders [42,43].…”
Section: Discussionmentioning
confidence: 99%